Didactic proposal for the teaching of economics. Part II (2021)
This article briefly illustrates the history of didactics and of the multiple notions that have been put forward from various perspectives. The article also discusses some of the most important teaching developments and gives an explanation of the relationship between dialectics and learning. The article presents some general ideas regarding the teaching of economics, invites a reflection on students' learning, and presents a particular strategy that has been put in place in the UCPR Economics Department: professor and student research groups.